Ginsenosides as epigenetic modulators: HDAC, DNMT, and miRNA-targeted mechanisms in tumour suppression - Neha Saini; Falguni goel; Mithun Singh Rajput (Molecular Biology Reports, 2026)

Deposition of Particulate Matter on Roadside Plant Leaves in Urban Environment (New Delhi): Implications to Plant Health - Supreet Kaur; Neha Gandhi; Sumit Kumar Mishra; Amit Kumar Goswami; Vikas Goel; Mamta Devi; Kartika Pandey (Aerosol Science and Engineering, 2026)

A sequential downstream strategy for polychromatic proteins from Spirulina platensis: integrating thermo-mechano-chemical disruption with high-yield fractionation - Neha Goel; Poonam Choudhary (Bioresource Technology Reports, 2026)

Integration of Conjugated Linoleic Acid–Producing Probiotic Strains Having Anti-adipogenic Properties with Honey and Oyster Mushrooms for the Formulation of Non-dairy Probiotic Beverage - Neha Baliyan; Abhishek Goel; Sanjeev Kumar Sharma; Mahesh Gupta; Yogendra Padwad; Rakshak Kumar (Probiotics and Antimicrobial Proteins, 2026)

Phosphodiesterase-4 Inhibition: An Experimental Approach to Overcome Drug Resistance in a Rotenone-Corneal 6 Hz Kindling Mouse Model of Drug-Resistant Epilepsy - Neha Tiwari; Arvinder Kaur; Arshbir Kaur; Rajesh Kumar Goel (Molecular Neurobiology, 2026)

Molecular cloning, expression, purification and functional characterization of Rv1588c of Mycobacterium tuberculosis - Neha Goel; Dheeraj Singh; Amitava Bandhu (Biocatalysis and Agricultural Biotechnology, 2024)

Trichoderma Mediated Metal Chelator and Its Role in Solanum melongena Growth Under Heavy Metals - Gaurav Yadav; Neha Sharma; Arti Goel; Ajit Varma; Arti Mishra; S. L. Kothari; D. K. Choudhary (Journal of Plant Growth Regulation, 2024)

Transcriptome analysis unravels RNAi pathways genes and putative expansion of CYP450 gene family in cotton leafhopper Amrasca biguttula (Ishida) - Mridula Gupta; Satnam Singh; Gurmeet Kaur; Suneet Pandher; Noorpreet Kaur; Neha Goel; Ramandeep Kaur; Pankaj Rathore (Molecular Biology Reports, 2021)

Genetics of Fe, Zn, β-carotene, GPC and yield traits in bread wheat (Triticum aestivum L.) using multi-locus and multi-traits GWAS - Jitendra Kumar; Gautam Saripalli; Vijay Gahlaut; Neha Goel; Prabina Kumar Meher; Kaushlesh Kumar Mishra; Prafulla Chandra Mishra; Deepmala Sehgal; Prashant Vikram; Carolina Sansaloni; Sukhwinder Singh; Pradeep Kumar Sharma; et al. (Euphytica, 2018)

Genome-Wide Analysis in Wild and Cultivated Oryza Species Reveals Abundance of NBS Genes in Progenitors of Cultivated Rice - Hukam C. Rawal; S. V. Amitha Mithra; Kirti Arora; Vishesh Kumar; Neha Goel; Dwijesh Chandra Mishra; K. K. Chaturvedi; Anil Rai; S. Vimala Devi; T. R. Sharma; Amolkumar U. Solanke (Plant Molecular Biology Reporter, 2018)

Effect of Allelic Variation in Triticin on Bread- and Chapati-Making Qualities of Wheat (Triticum aestivum) - Sonia Goel; Meenal Rathore; Sapna Grewal; Neha Jain; Binay K. Singh; Arvind K. Ahlawat; Anju M. Singh; Pradeep K. Singh; Nagendra K. Singh (Agricultural Research, 2015)

clpC operon regulates cell architecture and sporulation in Bacillus anthracis - Lalit K. Singh; Neha Dhasmana; Andaleeb Sajid; Prasun Kumar; Asani Bhaduri; Mitasha Bharadwaj; Sheetal Gandotra; Vipin C. Kalia; Taposh K. Das; Ajay K. Goel; Andrei P. Pomerantsev; Richa Misra; et al. (Environmental Microbiology, 2015)
Summary The clpC operon is known to regulate several processes such as genetic competence, protein degradation and stress survival in bacteria. Here, we describe the role of clpC operon in B acillus anthracis . We generated knockout strains of the clpC operon genes to investigate the impact of CtsR , McsA , McsB and ClpC deletion on essential processes of B . anthracis. We observed that growth, cell division, sporulation and germination were severely affected in mcsB and clpC deleted strains, while none of deletions affected toxin secretion. Growth defect in these strains was pronounced at elevated temperature. The growth pattern gets restored on complementation of mcsB and clpC in respective mutants. Electron microscopic examination revealed that mcsB and clpC deletion also causes defect in septum formation leading to cell elongation. These vegetative cell deformities were accompanied by inability of mutant strains to generate morphologically intact spores. Higher levels of polyhydroxybutyrate granules accumulation were also observed in these deletion strains, indicating a defect in sporulation process. Our results demonstrate, for the first time, the vital role played by McsB and ClpC in physiology of B . anthracis and open up further interest on this operon, which might be of importance to success of B . anthracis as pathogen.

Impaired conflict monitoring in Parkinson’s disease patients during an oculomotor redirect task - Ausaf A. Farooqui; Neha Bhutani; Shrikanth Kulashekhar; Madhuri Behari; Vinay Goel; Aditya Murthy (Experimental Brain Research, 2011)